The Social and Religious Designs of J. S. Bach's Brandenburg Concertos - Marissen, Michael (Book collections on Project MUSE., 1995)
This new investigation of the Brandenburg Concertos explores musical, social, and religious implications of Bach's treatment of eighteenth-century musical hierarchies. By reference to contemporary music theory, to alternate notions of the meaning of ""concerto, "" and to various eighteenth-century conventions of form and instrumentation, the book argues that the Brandenburg Concertos are better understood not as an arbitrary collection of unrelated examples of ""pure"" instrumental music, but rather as a carefully compiled and meaningfully organized set. It shows how Bach's concertos challenge